2017
DOI: 10.1002/gj.3052
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical, zircon U–Pb–Hf, and whole‐rock Sr–Nd isotopic study of Late Jurassic Sanming A‐type granite in the Wuyi area, Fujian province, Southeast China

Abstract: The Sanming pluton is the only Late Jurassic A‐type granitic intrusion in the Wuyi area, west Fujian Province, Southeast China, and its formation has important implications for our understanding of the tectonic evolution of the region. The U–Pb ages of 157 ± 1 Ma and 159 ± 1.1 Ma were obtained for the pluton by zircon LA–ICP–MS analysis, which is interpreted to be the crystallization age of the Sanming pluton (i.e., Late Jurassic). The pluton has the geochemical characteristics of A‐type granite, such as high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…All zircon grains show clear oscillatory zoning, which is consistent with a magmatic origin. And they show very high Th/U ratios (all >0.5), similar to typical magmatic zircons (Belousova et al, 2002; Hoskin & Schaltegger, 2003; Wu & Zheng, 2004; Zhao, Jiang, Yu, et al, 2017; Zhao, Yu, Mao, et al, 2017). RTW3436‐1: Zircon grains from samples RTW3436‐1 show very clear and narrow oscillatory zoning, similar to magmatic zircons.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…All zircon grains show clear oscillatory zoning, which is consistent with a magmatic origin. And they show very high Th/U ratios (all >0.5), similar to typical magmatic zircons (Belousova et al, 2002; Hoskin & Schaltegger, 2003; Wu & Zheng, 2004; Zhao, Jiang, Yu, et al, 2017; Zhao, Yu, Mao, et al, 2017). RTW3436‐1: Zircon grains from samples RTW3436‐1 show very clear and narrow oscillatory zoning, similar to magmatic zircons.…”
Section: Resultsmentioning
confidence: 69%
“…They exhibit strong negative Nb, Ta and Ti anomalies and positive Zr and Hf anomalies on the primitive‐mantle normalized trace element spider diagrams (Figure 5b). The strong negative Nb–Ta and Ti anomalies normally indicate the high crystallization of the Ti‐bearing minerals, including ilmenite, rutile, and titanite (Foley et al, 2002; Green, 1995; Manning & Bohlen, 1991; McDonough, 1991; Rudnick et al, 2000; Zhao, Jiang, Yu, et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that the North Wuyi terrane collided and merged with the East Wuyi terrane at 450–440 Ma (e.g., Zhao et al, 2017, 2019; Zhao, Jiang, Xing, et al, 2018; Zhao, Jiang, Yu, et al, 2018; Zhao, 2022). However, the detailed evolution between the North and South Wuyi terranes remains controversial and understated.…”
Section: Introductionmentioning
confidence: 99%
“…Mesozoic large‐scale magmatism and associated ore formation in South China peaked during three intervals: at ca. 230–210 Ma, 160–150 Ma, and 90–70 Ma (Feng, Zhang, Zeng, & Wang, ; Hu & Zhou, ; Li et al, ; Mao et al, ; Wang et al, ; Zhao, Jiang, Yu, Xing, & Yu, ). Compared to the well‐studied Jurassic ore‐forming events, the Late Triassic and Late Cretaceous mineralization stages have been less thoroughly investigated to date, especially in the Nanling Range (Chen, Wang, Zhu, Lu, & Ma, ; Wu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Mesozoic large-scale magmatism and associated ore formation in South China peaked during three intervals: at ca. 230-210 Ma, 160-150 Ma, and 90-70 Ma (Feng, Zhang, Zeng, & Wang, 2012; FIGURE 1 Distribution of Mesozoic granites in South China (after Cai et al, 2015), showing the location of the Dengfuxian and Xitian ore fields [Colour figure can be viewed at wileyonlinelibrary.com] Zhou, 2012;Li et al, 2016;Mao et al, 2013;Wang et al, 2011;Zhao, Jiang, Yu, Xing, & Yu, 2017). Compared to the well-studied Jurassic ore-forming events, the Late Triassic and Late Cretaceous mineralization stages have been less thoroughly investigated to date, especially in the Nanling Range (Chen, Wang, Zhu, Lu, & Ma, 2014;Wu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%